2023
DOI: 10.3390/molecules28020582
|View full text |Cite
|
Sign up to set email alerts
|

The Current State and Future Prospects of Auricularia auricula’s Polysaccharide Processing Technology Portfolio

Abstract: Auricularia auricula polysaccharides (AAP) have been widely studied in the field of medicine and healthcare because of their unique structure and physiological activity. Many species of Auricularia auricula polysaccharides have been extracted, isolated, and purified by different methods, and their structures have been analyzed. Auricularia auricula polysaccharides have been proven to have beneficial effects on the human body, including slowing the aging process, controlling the intestinal system, and treating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…Table 1 summarizes the preparation of PIC from different sources by using the iron chloride co-heating method. [13,[22][23][24][25][26][27][28][29][30][31][32][33] The reaction principle is roughly as follows: sodium citrate is used as a catalyst to catalyze the reaction between iron chloride and polysaccharides. NaOH is used to adjust the pH to generate a reddish brown precipitate.…”
Section: Iron Chloride Co-thermal Synthesis Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 1 summarizes the preparation of PIC from different sources by using the iron chloride co-heating method. [13,[22][23][24][25][26][27][28][29][30][31][32][33] The reaction principle is roughly as follows: sodium citrate is used as a catalyst to catalyze the reaction between iron chloride and polysaccharides. NaOH is used to adjust the pH to generate a reddish brown precipitate.…”
Section: Iron Chloride Co-thermal Synthesis Methodsmentioning
confidence: 99%
“…32.88 [13] cycle, and quality control. [21] In addition, other preparation methods have been reported in some literature.…”
Section: Codonopsismentioning
confidence: 99%
See 1 more Smart Citation
“…The mushroom Auricularia auricular , which is known for its medicinal properties [ 234 ] and anti-sickling potential, was recently studied in Nigeria. The study showed that this functional food, which has strong free radical scavenging activity, may reverse and stabilize erythrocyte membrane integrity and morphology.…”
Section: Nutritional Perspectives In Sickle Cell Diseasementioning
confidence: 99%
“…The main cultivation process is bagging cultivation in greenhouse, which comes from traditional agronomy. It costs more manpower and material resources and is not suitable for automation and intelligent control [1,2] . Many studies have been conducted on cultivation techniques and alternatives substrate for fungus cultivation.…”
Section: Introduction mentioning
confidence: 99%